Molecular Karyotyping of Human Single Sperm by Array- Comparative Genomic Hybridization - Patassini, Cristina; Garolla, Andrea; Bottacin, Alberto; Menegazzo, Massimo; Speltra, Elena; Foresta, Carlo; Ferlin, Alberto (PloS one, 2013)
No valid method is currently available to analyze the entire genome of sperm, including aneuploidies and structural chromosomal alterations. Here we describe the optimization and application of array-Comparative Genomic Hybridization (aCGH) on single human sperm. The aCGH procedure involves screening of the entire chromosome complement by DNA microarray allowing having a molecular karyotype, and it is currently used in research and in diagnostic clinical practice (prenatal diagnosis, pre-implantation genetic diagnosis), but it has never been applied on sperm. DNA from single human sperm isolated by micromanipulator was extracted, decondensed and amplified by whole-genome amplification (WGA) and then labeled, hybridized to BAC array, and scanned by microarray scanner. Application of this protocol to 129 single sperm from normozoospermic donors identified 7.8% of sperm with different genetic anomalies, including aneuploidies and gains and losses in different chromosomes (unbalanced sperm). On the contrary, of 130 single sperm from men affected by Hodgkin lymphoma at the end of three months of chemotherapy cycles 23.8% were unbalanced. Validation of the method also included analysis of 43 sperm from a man with a balanced translocation [46,XY,t(2;12)(p11.2;q24.31)], which showed gains and losses corresponding to the regions involved in the translocation in 18.6% of sperm and alterations in other chromosomes in 16.3% of sperm. Future application of this method might give important information on the biology and pathophysiology of spermatogenesis and sperm chromosome aberrations in normal subjects and in patients at higher risk of producing unbalanced sperm, such as infertile men, carriers of karyotype anomalies, men with advanced age, subjects treated with chemotherapy, and partners of couples with repeated miscarriage and repeated failure during assisted reproduction techniques.